Factors Influencing Distress and Coping Strategies Among Patients with Metastatic Spinal Tumor at Cipto Mangunkusumo General Hospital - Agiananda, Feranindhya; Nugraeni, Tiara; Diatri, Hervita; Aninditha, Tiara; Kusumaningrum, Profitasari (Indonesian Journal of Cancer, 2023)
Background: Patients with metastatic spinal tumor are experiencing various symptoms, including neurological deficits that cause distress and affects their quality of life. The vulnerability to distress is influenced by coping strategies. Therefore, this study aimed to investigate factors associated with distress and coping strategies in patients with metastatic spinal tumors at Cipto Mangunkusumo General Hospital. Methods: In a cross-sectional study conducted at Cipto Mangunkusumo General Hospital from September 2021 to May 2022, factors associated with distress and coping strategies in patients with metastatic spinal tumors were investigated. The analysis included a total of 104 subjects from both outpatient and inpatient settings. Distress levels and areas of concern were assessed using the Distress Thermometer (DT) questionnaire while coping strategies were evaluated through the Coping Orientation to the Problem Experienced (COPE) instrument. Bivariate and multivariable analyses were carried out to assess the relationship between sociodemographic factors, spinal tumor characteristics, specific areas of concern, coping strategies, and distress.Results: The results showed that 57.7% of metastatic spinal tumor patients experienced distress. In the 18-59 age group, motor disorders, sensory disturbances, autonomic disorders, treatment status, problem-focused coping (PFC), emotion-focused coping (EFC), and avoidance coping had significant associations with distress. However, the multivariable analysis showed that EFC (OR = 1.156, 95% CI: 1.024–1.304, p=0.019), avoidance coping (OR = 1.154, 95% CI: 1.005–1.326, p=0.042), and sensory disturbance (OR = 16.001, 95% CI: 1.472–173.960, p=0.023) were identified as risk factors for distress.Conclusions: Patients with metastatic spinal tumors who used emotion-focused coping, avoidance coping, and sensory disturbance faced significant risk factors for distress